Variants of MMP-9 and TIMP-1 Levels Could be a Predictor of an Early Development of Cardiovascular Diseases in Type 2 Diabetes among Iraqi Patients - Abdul Wadood, Shatha; Al Shawk, Refif; Hashem, Rusul (Iraqi Journal of Science, 2023)
Dysregulation of matrix metalloproteinases-9 (MMP-9) and tissue inhibitors ofmatrix metalloproteinases-1 (TIMP-1) may contribute to the development ofcardiovascular diseases in type 2 diabetes mellitus (T2DM) patients. The aim of thisstudy was to determine the effects of chronic hyperglycemia on serumconcentrations of MMP-9 and TIMP-1of T2DM patients without dyslipidemia (oneof atherosclerosis risk factors) and with duration less than 5 years in comparisonwith T2DM patients with dyslipidemia and with duration more than 10 years andcontrols. Also to investigate if serum levels of MMP-9 and TIMP-1 could bepotential markers for early detection of the development of cardiovascularcomplications in T2DM patients without dyslipidemia. This study consisted of 24T2DM patients without dyslipidemia, 30 T2DM patients with dyslipidemia, and 26healthy subjects. A variety of inflammatory markers including: MMP-9, TIMP-1,IL18 and hs-CRP were compared among the three groups. The BMI was similaramong the three groups. A significant increase of WHR, WHtR, FPG, TC, TG,LDL-C, VLDL-C, AIP, atherogenic ratio-1, atherogenic ratio-2, hs-CRP, MMP-9,TIMP-1 and IL-18 with a significant decrease of HDL-C, β Cell% and S% amongthe three groups. MMP-9 of T2DM patients without dyslipidemia and with durationless than 5 years showed a significant positive correlation with FPG and asignificant negative correlation with TC. MMP-9 of T2DM patients withdyslipidemia and with duration more than 10 years showed significant negativecorrelation with LDL-C. TIMP-1 of T2DM patients with dyslipidemia and withduration more than 10 years showed a significant negative correlation with TC, TG,VLDL-C and atherogenic ratio-1. The significant increased levels of both MMP-9and TIMP-1 in T2DM patients without dyslipidemia and with duration less than 5years compared to controls showed that those patients have risk factor forcardiovascular complications. This study suggests that MMP-9 and TIMP-1 may bepotentially useful as markers in T2DM patients at risk of progression ofcardiovascular diseases.